Price Dispersion and Stockpiling by Consumers - Bucovetsky, Sam (Review of Economic Studies, 1983)
This paper presents a model of equilibrium price dispersion in which buyers do not search. However they are able to store the non-durable commodity for future use. Such behaviour implies sellers' demand curves are endogenously generated by the observed price distribution. Equilibrium is shown to exist. Although more than one price may be charged in equilibrium, the monopoly price will occur with positive probability. Comparative static results are derived with a linear version of the model, some of which are "perverse".